Gending Dalam Prosesi Panggih Pengantin G.K.R. Hayu Dan K.P.H. Notonegoro di Keraton Yogyakarta - RITA APRIANI (Saraswati)
Wedding magnificient and glorious place in this year, was in the palace of Yogyakarta. This procession is a procession that is rare because unlike wedding ceremony in general. Especially in ceremonial procession and presentation of Javanese music. But here will discussed more in the presentation of Javanese music, for commonly called Javanese music “gending”, especially the traditional ceremonies Panggih. Which will reviewed that is:Lancaran Bindri, laras slendro patet sanga; Ladrang Temanten, laras pelog patet barang; Gending Boyong dhawah Ladrang Boyong laras pelog patet barang.Keywords: gending, panggih, Keraton Yogyakarta.